Effect of stress and intesity of mobile phone using on the health and subjective symptoms in GSM workers - Agata Szyjkowska; Elżbieta Gadzicka; Wiesław Szymczak; Alicja Bortkiewicz (Nofer Institute of Occupational Medicine, 2017)
Background: There are no available data on the health consequences that may result from the synergistic effects of electromagnetic fields (EMF) and stress. Understanding the mechanisms of the simultaneous exposure will make it possible to develop procedures to minimize adverse health effects in professionals using mobile phones. Material and Methods: A questionnaire survey was conducted in 600 randomly selected people to obtain data on their health status and the prevalence of subjective symptoms related to the mobile phones using. Among them, there were 208 GSM Network employees, to whom the Perceived Stress Scale and Assessment of Stress at Work Questionnaire were sent. Eighty-nine completed questionnaires were returned (response rate - 42.8%). Results: The mean age of respondents was 30.3 years (standard deviation (SD) = 7.7), time of occupational use of mobile phone - 4.1 years (SD = 1.7), the level of occupational stress - 95.3 (SD = 19.1). A significant percentage of people (62.8%) complained of the frequent difficulties in coping with problems of everyday life, and 57.4% had a fairly frequent problems with managing their own affairs. Significant differences in the life stress were detected between groups with different time of phone use (p = 0.03), and in occupational stress level, significant differences were noted between the 2 groups differing in the length of the conversation (p = 0.05). The risk of headache, associated (odds ratio (OR) = 4.2, p = 0.008) or not associated (OR = 2.97, p = 0.04) with calls on mobile phone, adjusted for stress, was significantly higher in people speaking via mobile more than 60 min/day than in those talking less. Conclusions: The study indicates that both stressors acting at the same time (EMF from cell phone and stress) adversely affect the well-being of workers and increase the risk of subjective symptoms. Med Pr 2017;68(5):617-628